2016
DOI: 10.1016/j.jams.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Norepinephrine Mediates Acupunctural Effects on Hypothalamic–Pituitary–Adrenal Axis During Ethanol Withdrawal

Abstract: A previous study demonstrated that acupuncture at ST36 (Zu-San-Li) attenuates ethanol withdrawal (EW)-induced hyperactivation of the hypothalamic-pituitary-adrenal axis in rats. The current study investigated the involvement of hypothalamic norepinephrine (NE) in that process. Rats were intraperitoneally treated with 3 g/kg/d of ethanol or saline for 28 days. After 24 hours of EW, acupuncture was applied to rats at bilateral ST36 points or at nonacupoints (tail) for 1 minute. A high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…reported that the anti-nociceptive action of caffeine is mediated by norepinephrine signaling in the locus coeruleus and spinal cord 20 . In contrast, several studies reported that acupuncture attenuates norepinephrinergic transmission 28, 29 . Thus, acupuncture may counteract the anti-nociceptive action of caffeine, resulting in an apparent increase of mechanosensitivity.…”
Section: Discussionmentioning
confidence: 96%
“…reported that the anti-nociceptive action of caffeine is mediated by norepinephrine signaling in the locus coeruleus and spinal cord 20 . In contrast, several studies reported that acupuncture attenuates norepinephrinergic transmission 28, 29 . Thus, acupuncture may counteract the anti-nociceptive action of caffeine, resulting in an apparent increase of mechanosensitivity.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, acupuncture regulates the metabolism of catecholamines. Acupuncture decreases levels of norepinephrine and epinephrine in the plasma and renal tissues of spontaneously hypertensive rats 109 and levels of norepinephrine in the hypothalamus of alcoholic rats 117 . Thus, acupuncture may alleviate pain and reduce neuroinflammation, in part, by restoring deficiencies in catecholamine metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulated evidences demonstrate that the neurotransmitter systems, such as norepinephrine, glutamate, serotonin and dopamine, elicit effects on NTs . It is possible to facilitate the release of a certain transmitter in the CNS and subsequent activation of a related receptor and downstream signaling pathway by means of acupuncture or EA . Accordingly, the modulation of neurotransmitter system may be one candidate potential mechanism underlying the regulation of neural plasticity by acupuncture.…”
Section: Discussionmentioning
confidence: 99%